(3GdhUdI Edi GdMHjH aj hUa GdWjHGJ hGdWjHs - (3YeQ Hf CMeO Hf gHI Gddg Hf CHj LQGOI GdYbjdj, ceGd GdOjf GHf GdYOje,J (B660 (3g` s ((3eMeO Hf Ydj GdefGhj GdfGSN s)
(3ChdgG (B:s
(3hHYO aEfg deG cGf eYXe GddPGJ GdOfhhjI s
(3BNQgG (B:s
(3hjUfY efg MHkG hjLaa aj GdXd hojSJYed ceG JbOe PcQg hef efGaYg TaGA GdNabGf hGddg CYde s
(3PcQJ HYV GdeUGOQ Cf GdeDda gh Hf GdYOje GdMdHi hgPG ZjQ eDcOs
(3fSNI QGHYI NRGFfjIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B40 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B275s
Keywords: (3GdUfGYI hGdCWYeIs